Study of Corylus cornuta twig extracts: antioxidant, radical scavenging, anti-enzymatic activities and cytotoxicity - Royer, Mariana; Stevanovic, Tatjana (International Journal of Biotechnology for Wellness Industries, 2012)
In a fist attempt to better understand therapeutic uses of the forest species Corylus cornuta by Native People of Eastern Canada, antiradical/antioxidant, anti-enzymatic activities as well as cytotoxicity on Normal Human Keratinocytes (NHK) of C.cornuta twig extracts were studied and correlated with their polyphenolic composition. Polyphenolic extracts were obtained by water and ethanolic extractions using two different techniques: maceration and ultrasound-assisted extraction. Antiradical and antioxidant capacities of the extracts were evaluated against DPPH, TEAC, six ROS/RNS and peroxidation lipidic. Anti-enzymatic activities against enzymes involved in oxidation processes were evaluated towards catalase and xanthine oxidase. MTT and Neutral Red assays were used for evaluating the toxicity of the various extracts on NHK after 24 and 48h exposition times. Aqueous extracts were determined to have the highest antioxidant/antiradical capacity against two reactive species involved in inflammatory processes (superoxide anion and nitric oxide) and the lowest toxicity. Their antioxidant/antiradical activities were strongly correlated to their higher content in flavonoids. Ethanolic extracts were determined to have the highest anti-enzymatic activity correlated with their higher content in hydroxycinammic acids and proanthocyanidins. These extracts were also the most toxic, this toxicity correlating with their high level in total phenols. Given that aqueous extracts presented an elevated content in total phenols and flavonoids and showed the lowest toxicity on NHK as well as a high antiradical/antioxidant capacity, they can be considered as the most valuable extracts obtained from C.cornuta twigs which is in harmony with traditional uses in which remedies are prepared from twig infusions.